(untitled) (Journal of the College of Basic Education, 2022)
Despite the peculiar richness of the theatrical corpus since the emergence of Greek Tragedy as a dramatic genre in the 5th century B.C. (Case 1985:318), little effort has been made to developing the theatre studies as a well-defined academic discipline. Noteworthy, in this context, is the dominance of writtentext analysis approach to theatre texts since Aristotle’s The Poetics (Kier 1980: 5).This situation gives rise to two far-reaching results. The first is related to the commonly-held view of the supremacy of literary/written text over the other elements of the theatrical show. The second result is concerned with the impact such an attitude had on translating theatre. In this respect, Susan Bassnett notes that "of all types of literary translation, theatre is the most neglected area."(1991: